Formation and implementation of the enterprise budgetingі - Савка, Ю. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The article reviews the main approaches to the definition of “budgeting”. We also consider the concept of “budgeting”. Designed the method of formation of the budgeting system in the enterprise to further the effective implementation and operation. In particular, investigated and determination of goals and objectives of the enterprise budgeting studied functions and principles of budgeting. Also investigated the influence budgeting management functions. The question of the formation of appropriate financial structure of the enterprise to function effectively budgeting. The basic types of budgets necessary for the proper management decisions. The basic approaches to attract workers to implement the enterprise budgeting. The basic problem of training enterprises to introduce budgeting.